2018
DOI: 10.1371/journal.pone.0201319
|View full text |Cite
|
Sign up to set email alerts
|

First trimester prenatal screening biomarkers and gestational diabetes mellitus: A systematic review and meta-analysis

Abstract: Biomarkers commonly assessed in prenatal screening have been associated with a number of adverse perinatal and birth outcomes. However, it is not clear whether first trimester measurements of prenatal screening biomarkers are associated with subsequent risk of gestational diabetes mellitus (GDM). We aimed to systematically review and statistically summarize studies assessing the relationship between first trimester prenatal screening biomarker levels and GDM development. We comprehensively searched PubMed/MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 42 publications
3
24
0
2
Order By: Relevance
“…Even a PAPP-A value <1 MoM was predictive of GDM, whereas a β-hCG value >2 MoM was inversely associated with GDM. Our findings are consistent with a couple of previous studies [11,16], other than a recent systematic review and meta-analysis [30], indicating that both reduced first trimester levels of PAPP-A and free β-hCG are associated with the risk of GDM development. In addition, our data are consistent with those reported in a large Thailandian population, indicating a specific protective effect against GDM of a β-hCG value >2 MoM [18].…”
Section: Discussionsupporting
confidence: 93%
“…Even a PAPP-A value <1 MoM was predictive of GDM, whereas a β-hCG value >2 MoM was inversely associated with GDM. Our findings are consistent with a couple of previous studies [11,16], other than a recent systematic review and meta-analysis [30], indicating that both reduced first trimester levels of PAPP-A and free β-hCG are associated with the risk of GDM development. In addition, our data are consistent with those reported in a large Thailandian population, indicating a specific protective effect against GDM of a β-hCG value >2 MoM [18].…”
Section: Discussionsupporting
confidence: 93%
“…The relationship with metabolism has been studied especially for Gestational Diabetes Mellitus (GDM). Several studies found that, in the first trimester of pregnancy, the values of PAPP-A levels were lower in patients who developed GDM, compared to patients with normoglycemic pregnant, suggesting a possible role of this biochemical marker in GDM screening in early pregnancy 34,35 . From these data it can be deduced that low PAPP-A concentrations could be an indicator of a pathophysiological process that will lead to GDM and type 2 DM years after pregnancy, but which is already in place months before the disease becomes striking.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Donovan et al [ 286 ] included 13 studies and 83,921 subjects (GDM n = 3786). While the study identified a high degree of heterogeneity mostly due to the analysis method, the GDM diagnostic criteria and the ethnicity of subjects involved, the overall analysis and sub-analysis identified significantly lower first-trimester PAPP-A levels in women who developed GDM compared with controls with even lower levels in GDM women diagnosed prior to 24 weeks of gestation.…”
Section: Cytokinesmentioning
confidence: 99%